Insights From Analysis of Human Antigen-Specific Memory B Cell Repertoires - Shah, Hemangi B.; Smith, Kenneth; Wren, Jonathan D.; Webb, Carol F.; Ballard, Jimmy D.; Bourn, Rebecka L.; James, Judith A.; Lang, Mark L. (Frontiers in Immunology, 2019)
Memory B cells that are generated during an infection or following vaccination act as sentinels to guard against future infections. Upon repeat antigen exposure memory B cells differentiate into new antibody-secreting plasma cells to provide rapid and sustained protection. Some pathogens evade or suppress the humoral immune system, or induce memory B cells with a diminished ability to differentiate into new plasma cells. This leaves the host vulnerable to chronic or recurrent infections. Single cell approaches coupled with next generation antibody gene sequencing facilitate a detailed analysis of the pathogen-specific memory B cell repertoire. Monoclonal antibodies that are generated from antibody gene sequences allow a functional analysis of the repertoire. This review discusses what has been learned thus far from analysis of diverse pathogen-specific memory B cell compartments and describes major differences in their repertoires. Such information may illuminate ways to advance the goal of improving vaccine and therapeutic antibody design.